Hubungan Minat Baca dan Penguasaan Kosakata dengan Pemahaman Bacaan Berbahasa Inggris - Jumatriadi Jumatriadi (ISLAMIKA, 2019)
This research is aimed at finding out the nature and strength of relationships between reading interest, vocabulary mastery with English reading comprehension, both separately and simultaneously. The research was conducted at students of first and second semester of Islamic Religion Education Department of STIT Palapa Nusantara Lombok-NTB with 50 students taken as samples using random sampling. The technique used to analyze data was the statistical technique of regression and correlation. The result of the research indicates that there are positive correlation between: (1) reading interest with English reading comprehension; (2) vocabulary mastery with English reading comprehension; and (3) reading interest and vocabulary mastery with English reading comprehension. Based on the result of the research, it can be concluded that English reading comprehension can be developed by increasing reading interest and vocabulary mastery.